A 20:1 synergetic mixture of cafedrine/theodrenaline accelerates particle transport velocity in murine tracheal epithelium via IP3 receptor-associated calcium release - Schmidt, Götz; Rienas, Gerrit; Müller, Sabrina; Edinger, Fabian; Sander, Michael; Koch, Christian; Henrich, Michael (Frontiers in Pharmacology, 2023)
Background: Mucociliary clearance is a pivotal physiological mechanism that protects the lung by ridding the lower airways of pollution and colonization by pathogens, thereby preventing infections. The fixed 20:1 combination of cafedrine and theodrenaline has been used to treat perioperative hypotension or hypotensive states due to emergency situations since the 1960s. Because mucociliary clearance is impaired during mechanical ventilation and critical illness, the present study aimed to evaluate the influence of cafedrine/theodrenaline on mucociliary clearance. Material and Methods: The particle transport velocity (PTV) of murine trachea preparations was measured as a surrogate for mucociliary clearance under the influence of cafedrine/theodrenaline, cafedrine alone, and theodrenaline alone. Inhibitory substances were applied to elucidate relevant signal transduction cascades. Results: All three applications of the combination of cafedrine/theodrenaline, cafedrine alone, or theodrenaline alone induced a sharp increase in PTV in a concentration-dependent manner with median effective concentrations of 0.46 µM (consisting of 9.6 µM cafedrine and 0.46 µM theodrenaline), 408 and 4 μM, respectively. The signal transduction cascades were similar for the effects of both cafedrine and theodrenaline at the murine respiratory epithelium. While PTV remained at its baseline value after non-selective inhibition of β-adrenergic receptors and selective inhibition of β1 receptors, cafedrine/theodrenaline, cafedrine alone, or theodrenaline alone increased PTV despite the inhibition of the protein kinase A. However, IP3 receptor activation was found to be the pivotal mechanism leading to the increase in murine PTV, which was abolished when IP3 receptors were inhibited. Depleting intracellular calcium stores with caffeine confirmed calcium as another crucial messenger altering the PTV after the application of cafedrine/theodrenaline. Discussion: Cafedrine/theodrenaline, cafedrine alone, and theodrenaline alone exert their effects via IP3 receptor-associated calcium release that is ultimately triggered by β1-adrenergic receptor stimulation. Synergistic effects at the β1-adrenergic receptor are highly relevant to alter the PTV of the respiratory epithelium at clinically relevant concentrations. Further investigations are needed to assess the value of cafedrine/theodrenaline-mediated alterations in mucociliary function in clinical practice.